THE INFLUENCE OF COMMUNICATION AND EMPLOYEE ACHIEVEMENT ON EMPLOYEE CAREER ADVANCEMENT AT THE PEKANBARU BRANCH OF PNM MEKAAR - Oktayudra, Farhan; Pratikno, Yuni; Firdaus, Ahmad (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
The purpose of this study was to determine the partial and simultaneous effects of communication, employee achievement on employee career advancement with the population being employees of PNM Mekaar Pekanbaru Branch totaling 193 employees, the sampling technique used the slovin formula, with a sample of 130 employees. Data analysis techniques using descriptive and inferential statistical analysis. The results showed that partially (t test) communication variables (X1) and employee achievement variables (X2) had an effect on employee career advancement (Y). While the simultas test (F test) shows that the communication variable (X1) and the employee achievement variable (X2) simultaneously have a significant effect on improving employee careers (Y). The R Square value of 0.630 means that communication and employee achievement have an influence of 63% on improving employee careers while the remaining 37% is influenced by other factors that are not included in this research model.